If climate change means more intense and more frequent drought, what will that mean for agricultural production? A case study in Northern Australia. Issue 3 (2nd July 2016) - Thi Tran, Lai; Stoeckl, Natalie; Esparon, Michelle; Jarvis, Diane
ABSTRACT: We examine the influence of drought and a variety of factors on agriculture in Northern Australia. Assuming constant prices, and using data collected from northern land managers, we estimate a Cobb–Douglas production function and use coefficients from the model to estimate the financial losses associated with drought. We find that drought-affected properties earn about half as much as other 'similar' properties. We then ask: How much does that ' cost ' the industry, on average, and how would those costs change if droughts were to become more, or less widespread under climate change ? Our estimates indicate that under the current climatic regime, the Northern Australian agricultural industry loses, on average, about 19% of output to drought each year: this could fall to 10% or rise to 40% under current climate projections. Although focused on Northern Australia, the findings have wider implications for management and adaption, given the magnitude of impacts and their likelihood to extend beyond the 'official' end of drought. Investments in climate-proof crops, on-farm management techniques and financial arrangements to help producers deal with a range of climatic risks, for example, should thus be priorities.